Optical Injection Locking for Generation of Tunable Low-Noise Millimeter Wave and THz Signals - Gleb Nazarikov (MDPI AG, 2021)
This article presents the experimental demonstration of synchronization of two integrated semiconductor distributed Bragg reflector lasers, fabricated with a generic multiproject wafer platform, by means of injection locking. Substantial linewidth reduction and frequency stabilization of the lasers were shown during locking of the lasers to an optical frequency comb. Phase noise was measured for different injected powers and different laser cavities. For a generation of millimeter-wave signals up to 80 GHz, two lasers were simultaneously locked to the comb. Fine-tuning was performed by tuning the repetition rate of the comb and coarse-tuning was carried out by switching to another comb line. A suppression ratio of 37 dB was achieved for unwanted comb lines. The achieved signal purity, phase noise, and suppression of unwanted components demonstrate the viability of injection locking for the generation of high-quality signals at sub-THz and THz frequencies and with substantial tunability.